Islamic and ethical finance in the United Kingdom - Housby, Elaine S. (Edinburgh guides to Islamic finance, 2013)
Islamic finance is routinely described as ethical. This reflects the fact that self described 'ethical' finance is a large and growing sector of the market. This book examines a wide range of financial institutions in Britain which fall broadly within the ethical sector